ANALISIS FAKTOR PENYEBAB WASTE PADA PROYEK KONSTRUKSI GEDUNG DI KOTA SURABAYA DENGAN METODE EXPECTED MONETARY VALUE - Bramantya Fidiansyah Putra; I Putu Artama Wiguna (Journal of Civil Engineering, 2019)
Generally, the term of waste can be defined as activities that cost both directly or indirectly and use physical and non-physical resources, but it does not add value or progress for the product. Waste occurring in a construction project could be in physical or non-physical form. A lot of main factors cause the existence of waste in a construction project, which are internal factors and external factors. Surabaya is a big city having the high growth-rate of building construction, so there are many projects buildings now. The probability of waste existence can be high too, because of this non-stop building procces.This research aims to find the main cause of waste in the project and the influence of its mitigation.The population of this research is building constuction projects in Surabaya that generate waste. The sampling technique is purposive technique sampling. This study uses data collection techniques by questionnaires and interviews about the factors that cause waste in 15 building construction projects. The taken data are probilities, and impact of waste cause variables. This research uses Fault Tree Analysis method, Monte Carlo, and Expected Monetary Value.. This number of probability dan the impact of the factors are calculated to gain the expected monetary value. The greatest value of this number indicates the main waste factor. The result of this research indicates three biggest cause of waste based on EMV value. They are owner making design change when construction have been running, less competent planners, and miscommunication happened in design planning. While, the largest category of waste causes is design category.